Free radical scavenging activity of Pterogyne nitens Tul. (Fabaceae) - Regasini, Luis Octavio [UNESP]; de Oliveira, Camila Martins [UNESP]; Rebuglio Vellosa, Jose Carlos [UNESP]; Mascarenhas de Faria Oliveira, Olga Maria [UNESP]; Siqueira Silva, Dulce Helena [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (Academic Journals, 2008)
As part of our ongoing research on antioxidant agents from Brazilian flora, twenty extracts and fractions obtained from Pterogyne nitens Tulasne (Fabaceae) were screened for free radical scavenging activity by using ABTS [2,2'-azinobis(3-ethylenebenzothiazoline-6-sulfonic acid)] and DPPH (2,2diphenyl- 1-picrylhydrazyl-hydrate) radicals colorimetric assay and beta-carotene bleaching test. The strongest activity was found in ethyl acetate fraction from the stem barks, exhibiting IC(50) values (in mu g/ml) of 2.10 +/- 0.1 and 10.2 +/- 0.3 on ABTS(center dot+) and DPPH(center dot), respectively. Additionally, chromatographic fractionation of stem barks yielding myricetin, quercitrin and mirycetrin, three flavonols with remarkable antioxidant activity.
Keywords: Antioxidant; free radical scavenging activity; DPPH; ABTS; Pterogyne nitens; Leguminosae; Fabaceae; Caesalpinioideae; flavonoid; flavonol